Strengthening Legal Frameworks for Managing Iraq’s Cultural Heritage Revenues: Memperkuat Kerangka Hukum untuk Mengelola Pendapatan Warisan Budaya Irak - Zghair, Haleemah Khlaif (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The protection of cultural heritage revenues in Iraq has become increasingly criticaldue to widespread looting, smuggling, and illegal exploitation, exacerbated by the country’s shiftingsecurity and economic conditions. Specific Background: Although Iraq possesses both domesticand international legal frameworks designed to safeguard its cultural heritage, their practicaleffectiveness remains hindered by implementation weaknesses and legal gaps. Knowledge Gap:There is limited research analyzing how existing laws can be optimized to ensure sustainablemanagement and protection of revenues derived from cultural heritage assets. Aim: This study aimsto evaluate the effectiveness of legal measures governing the protection and management of Iraqicultural heritage revenues, while proposing reforms to strengthen these frameworks. Results: Thefindings reveal that despite a robust legislative foundation, weak enforcement mechanisms andinsufficient inter-agency coordination impede optimal resource management. The researchhighlights the necessity of modernizing legislation and enhancing administrative processes.Novelty: By employing a comparative analytical approach, the study integrates insights frominternational practices to propose actionable reforms tailored to Iraq’s context. Implications: Thestudy underscores the importance of legislative updates, enhanced transparency, internationalcollaboration for asset recovery, and the establishment of a national fund to ensure the conservationand sustainable utilization of cultural heritage revenues. Highlights: Legal gaps weaken cultural heritage revenue protection. Global models guide legislative reform efforts. National fund ensures sustainable heritage management. Keywords: Cultural Heritage, Iraq, Legal Framework, Revenue Protection, Sustainable Management